141 Effect of induction of an ipsilateral vs. contralateral accessory corpus luteum (CL) on pregnancy per AI and pregnancy loss in lactating dairy cows. (30th November 2020) - Monteiro, Pedro L J; Gamarra, Caio A; Genari, Rodrigo S; Prata, Alexandre B; Barletta, Rafael V; Duran, Peregrino; Ochoa, Julian C; Canavessi, Aurea M O; Sartori, Roberto; Wiltbank, Milo C
Abstract: Induction of accessory CL can increase circulating progesterone (P4) and potentially improve fertility; although, regression of accessory CL contralateral to the pregnancy can occur, potentially negating their benefit. In this study, primiparous (n = 377) and multiparous (n = 678) lactating Holstein cows (80.0 ± 3.3DIM, 43.2 ± 13.3 kg milk/d, and BCS = 2.85 ± 0.24) were enrolled in Presynch-Ovsynch (PGF-14d-PGF-12d-GnRH-7d-PGF-56h-GnRH-16h-AI) with AI at 81 ± 3 DIM. On d5 after AI, cows were randomly but unequally assigned as Control (n = 289) or GnRH (n = 641; 100 µg gonadorelin acetate). Blood samples were collected for P4 and ovaries evaluated by ultrasound on d5, d12, d19, d26, d33, d47, and d61. mRNA for ISGs (d19) and PSPB (d26) concentrations were evaluated and pregnancy diagnoses were done on d26, d33, d47 (also embryonic measurements), and d61. Statistical analyses were performed with PROC GLIMMIX of SAS 9.4. Ovulation to GnRH on d5 was 85.4% (577/676). Cows were designated as: Control (n = 289), Ipsilateral (n = 239), or Contralateral (n = 241). Overall P4 differed (P < 0.01) within groups (Control = 7.90 ± 0.35 c, Ipsilateral = 10.5 ± 0.34 a, and Contralateral = 9.55 ± 0.26 a ). Interestingly, 52.7% (78/148) of contralateral pregnant cows had accessory CL regression by d61 with decreases in P4 after contralateral CL regression (P < 0.001). There were no treatment differences for pregnant cows in ISG15 (P = 0.63) or Mx2 (P = 0.51) mRNA, circulating PSPB (P = 0.56), amniotic vesicle size (P = 0.89), or crown-rump length (P = 0.19) or in pregnancy/AI on d26 (P = 0.24), d33 (P = 0.67), d47 (P = 0.53), or d61 (P = 0.62; overall 50.3% [387/769]). Nevertheless, pregnancy losses between d26 and d61 were lower (P = 0.03) for ipsilateral (6.6 ± 2.3%) than contralateral (14.0 ± 3.0%) and from controls (P = 0.065; 13.7 ± 2.9%) With differences also from d26-33 (Control = 7.5 ± 2.1; Ipsilateral = 3.1 ± 1.5; Contralateral = 9.6 ± 2.5). Within contralateral group, early accessory CL regression was associated with greater pregnancy loss from d26-33 (P = 0.04) and d26-61 (P = 0.01). Thus, induction of accessory CL increases P4 and may reduce pregnancy loss, although these advantages are reduced for contralateral accessory CL, because many of these CL regress during pregnancy.